Mental Health Among Incarcerated Women: an Examination of Factors Impacting Depression and PTSD Symptomology - Cabeldue, Mollimichelle (Women & criminal justice, 2019)
Female offenders experience mental health symptoms at a higher rate than male offenders and females in the community. The current study investigated individual characteristics and experiences that may impact symptoms of depressive disorders and posttraumatic stress disorder (PTSD) among a sample of female inmates in a large Southern prison system. Results showed high rates of reported childhood and adult victimization experiences among the sample. Factors such as seeking mental health treatment prior to incarceration significantly impacted the reporting of depressive and PTSD symptoms, as did victimization histories. Findings suggest that women would benefit from screening to identify mental health needs at the onset of incarceration as well as gender responsive needs assessment and programming to address histories of victimization and current mental health symptomatology.